Rehabilitation in the long-term care insurance domain: A scoping review - Hiroshi Shinohara; Yukio Mikami; Rumi Kuroda; Makoto Asaeda; Takashi Kawasaki; Ken Kouda; Yukihide Nishimura; Hiroyuki Ohkawa; Hiroyasu Uenishi; Toshio Shimokawa; Yasuo Mikami; Fumihiro Tajima; et al. (Health Economics Review, 2022)
Purpose: Since the enactment of the long-term care insurance (LTCI) act in 2000, the number of LTCI users has increased annually. However, evidence regarding what is being carried out as rehabilitation treatment under LTCI is lacking. In this study, a scoping review was performed to bridge this knowledge gap. Methods: Articles related to rehabilitation in connection with LTCI published between April 2000 and November 2020 were searched for in PubMed, CINAHL, CENTRAL (Cochrane Central Register of Controlled Trials), Ichushi Web Ver.5, and CiNii and randomized controlled trials (RCTs) of rehabilitation provided under LTCI were examined. Results: Of the 15,572 publications identifed, 15 RCTs, including rehabilitation treatment by physiatrists and therapists, met the eligibility criteria of our review and were included. The rehabilitation trials in the 15 RCTs varied and included balance training, exercise therapy, cognitive tasks, and activities such as singing and dancing. The results allowed us to focus on three categories: fall prevention, dementia, and theory and tools interventions related to occupational therapy practice. Conclusion: The focal points of attention in the rehabilitation treatment of LTCI were identifed. However, the physical function, quality of life, and activities of daily living (ADL) of those who 'need support' vary from person to person. Therefore, the consolidation of evidence on rehabilitation treatment of LTCI must be continued.
Keywords: 330; Dementia; Fall prevention; Long-term-care insurance; Occupational therapy model; Rehabilitation